Transdermal Drug Delivery - Ong, Yuhui (2016)
The mechanism of needle free injections technology (NFIT) works by using compressed gas as a pressure source to supply the drug with sufficient energy to penetrate through the skin at high speed. As each drugs have different molecular properties, operation parameters are varied accordingly. For this study, the main objective is to study the effects of the operation parameters on the shape of the liquid formed after the injection. An experimental model was set up which has a similar mechanism to that of NFIT. In the study, the material used was jelly which was made such that it had a similar Young Modulus to that of the human skin. With the material and set up ready, the experiment was conducted in two phases. The first part of the experiment used colored dye as the liquid for injection and the material to be injected was the jelly. The second part of the experiment used Poly (ethylene glycol) diacrylate (PEGDA) as the liquid for injection. For the experiments, parameters were varied to study the effects of each on the shape of the injected liquid. The variable parameters were the operation parameters which were frequency, number of pulses and pressure. The dependent parameters were the width, depth and penetration area of the injected liquid. Overall, the results showed that frequency and pressure had minimal effect on width of the injected liquid. Results also showed that pressure and number of pulses had a direct variation on the depth of the injected liquid while frequency had a reverse variation on the depth of the injected liquid. As for the penetration area, it was observed that when pressure and number of pulses were increased, the penetration area would increase. On the contrary, when frequency was increased, the penetration area would decrease. Lastly, a simulation was done using a software called COMSOL 5.0 to simulate the injection. The simulation results proved that the experimental results obtained were consistent. Therefore, we are able to validate the effects of operation parameters on the shape of the liquid after injection. In addition, simulation was done to simulate the injection of the liquid into the human skin. Through the simulation, we were able to find out that the shape of the injected liquid differs slightly in the human skin as compared to the jelly.